2004
DOI: 10.1016/j.aop.2004.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-exact solvability of Dirac–Pauli equation and generalized Dirac oscillators

Abstract: In this paper we demonstrate that neutral Dirac particles in external electric fields, which are equivalent to generalized Dirac oscillators, are physical examples of quasiexactly solvable systems. Electric field configurations permitting quasi-exact solvability of the system based on the sl(2) symmetry are discussed separately in spherical, cylindrical, and Cartesian coordinates. Some exactly solvable field configurations are also exhibited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 36 publications
0
51
0
1
Order By: Relevance
“…For the excited states, we cannot proceed the investigation as in the trigonometric case due to the lack of shape invariance. However, we can check by using the method of Bethe ansatz equations [6,7,12] that no elements of V ± N can be normalizable physical eigenstates except for the ground state ψ…”
Section: B Structure Of N -Fold Susymentioning
confidence: 99%
See 3 more Smart Citations
“…For the excited states, we cannot proceed the investigation as in the trigonometric case due to the lack of shape invariance. However, we can check by using the method of Bethe ansatz equations [6,7,12] that no elements of V ± N can be normalizable physical eigenstates except for the ground state ψ…”
Section: B Structure Of N -Fold Susymentioning
confidence: 99%
“…In view of the fact that so far all the N -fold SUSY potentials are only one-dimensional, it is natural that one should look for physical models which are effectively one-dimensional. Experience gained in the work in [6,7] suggests that Pauli and Dirac equations are good candidates to start with. In this respect we note that the authors of [24] found that if the Pauli equation is generalized such that the gyromagnetic ratio g = 2 of the electron is changed to some unphysical values g = 2N (N ≥ 2), then for certain forms of magnetic fields, the generalized Pauli equation could possess type A N -fold SUSY.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Later, several physical QES models were discovered, which include the two-dimensional Schrödinger [10], the Klein-Gordon [11], and the Dirac equation [12,13] of an electron moving in an attractive/repulsive Coulomb field and a homogeneous magnetic field. More recently, the Pauli and the Dirac equation minimally coupled to magnetic fields [14], and Dirac equation of neutral particles with non-minimal electromagnetic couplings [15] were also shown to be QES.…”
Section: Introductionmentioning
confidence: 99%